2012
DOI: 10.1007/s11357-012-9488-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel B cell population revealed by a CD38/CD24 gating strategy: CD38−CD24− B cells in centenarian offspring and elderly people

Abstract: The B cell arm of adaptive immunity undergoes significant modifications with age. Elderly people are characterized by impaired B cell responses reflected in a reduced ability to effectively respond against viruses and bacteria. Alterations of immunity with advancing age (immunosenescence) have been widely studied in centenarians who are considered a good example of successful aging. In recent years, attention has shifted to centenarian offspring (CO) as a model of people genetically advantaged for healthy agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 56 publications
3
53
0
Order By: Relevance
“…2a). A novel, potentially important TNF-producing CD24-CD38- B-cell population has been described by Buffa et al [17] and gated here (online suppl. fig.…”
Section: Resultsmentioning
confidence: 89%
“…2a). A novel, potentially important TNF-producing CD24-CD38- B-cell population has been described by Buffa et al [17] and gated here (online suppl. fig.…”
Section: Resultsmentioning
confidence: 89%
“…We have previously demonstrated that DN B cells from young and elderly donors are differently activated both in terms of proliferation [10] and cytokine production [50,51]. In recent years, Moir et al [23] have described the increase of an exhausted B cell population, named "tissue-like" B cells, in HIV-viraemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…They still express CD10, co-express IgD and IgM and present an activated phenotype with high expression of CD24 and CD38. [3][4][5] These cells home mainly to the spleen where they differentiate into CD27+IgM+ memory B-cells. 3 Immature-transitional B-cell frequencies are high in healthy children and slowly decrease with age until stable range levels are reached around 13 y of age.…”
Section: Overview On B-cell Development and Functionmentioning
confidence: 99%
“…31 Interestingly, B-cell immunophenotyping based on the activation markers CD24 and CD38 also revealed another population of CD24-CD38-B-cells to be increased in elderly individuals. 5 These cells produce the proinflammatory cytokine TNF-α which might contribute to the inflammatory status often observed in the elderly. 5 A summary of the effect of healthy aging on the different B-cell subpopulations has been incorporated in Table 1.…”
Section: B-cells During Healthy Agingmentioning
confidence: 99%
See 1 more Smart Citation